Data-driven review on gender and rice varietal trait preferences in Bangladesh - Khan, M.S.; Sarkar, M.A.R.; Islam, M.R.; Bhandari, H. (Frontiers Media, 2024)
In Bangladesh, farmers adapt to changing conditions through the adoption of improved varieties containing new or combined traits. The diverse varietal adoption decisions among farmers stem from gender-based differences in trait preferences. This review synthesizes existing knowledge to assess the nature, extent, and causes of gendered disparities in rice varietal trait preferences among farmers and consumers in Bangladesh. To enhance the data-driven nature of this review, we not only scrutinized secondary articles (45 documents) and databases but also incorporated and analyzed primary data on varietal adoption and trait preferences. The analysis revealed a pronounced need for rice breeding programs in Bangladesh to integrate both market and climate-smart traits, aligning with gender-specific needs in developing optimal rice product profiles. Analysis of primary data unveiled substantial variations in women and men farmers’ varietal trait preferences, influenced by factors like income, access to farming information, household size, land size, and decision-making. Consequently, addressing gender-differentiated trait preferences in the development of improved rice varieties is crucial to curtail farmers’ varietal adoption lag in Bangladesh. The findings underscore the necessity of systematic identification and integration of gender-differentiated varietal trait preferences into rice breeding programs. Failure to account for such preferences may disadvantage the gender-responsiveness of developed varieties and limit the anticipated impact. Therefore, understanding the biophysical, social, and cultural dynamics of diverse farmer groups from a gender perspective is imperative for achieving gender-responsive rice variety development in the context of Bangladesh. This process involves identifying key gender concerns for integration into rice breeding programs, ensuring a comprehensive approach to sustainable agriculture.